'Hesitant compliers': Qualitative analysis of concerned fully-vaccinating parents - Enkel, S.; Attwell, K.; Snelling, Thomas; Christian, H. (Elsevier, 2017)
Objective: Some parents are hesitant about vaccines and yet still vaccinate their children. Vaccine behaviours are not fixed and parents who are concerned but nonetheless adherent to standard schedules could switch to an unconventional schedule, delaying or cherry-picking vaccines. There is a need to better understand vaccine hesitancy in specific contexts, acknowledging cultural and geographical variation, to ensure interventions targeting hesitancy are well directed and received. Methods: To identify the behaviours, knowledge and attitudes of 'hesitant compliers' in Perth, Western Australia, nine one-on-one in-depth interviews were conducted with vaccinating parents of children ( < 5 years) who were identified as being hesitant. Interview transcripts were analysed qualitatively and themes developed inductively, following a constructivist paradigm. Results: Parents saw vaccination as important for themselves and their community, despite their limited knowledge of vaccine preventable diseases. Parents reported concerns about potential side effects, and worried about the safety of the measles-mumps-rubella (MMR) and seasonal influenza vaccines. Concerned about the role of anti-vaccination information in the community, some sought to isolate themselves from parents who did not vaccinate, although others were concerned that this could entrench non-vaccinators' behaviours. Parents' views were all underlaid by two pivotal 'vaccine-related events' that had occurred in the community: the severe injury of a baby from seasonal influenza vaccination in 2010, and the death of a baby from whooping cough in 2015. Conclusions: Parents interpreted pivotal vaccine-related events in the community as requiring them to take personal responsibility for vaccine decisions. Their reports of continued vaccine fears (evident in international studies in recent decades) demonstrate that vaccine scares have long lasting effects. With vaccine rates high and stable, current strategies appear to be have little impact on addressing parental vaccine concerns. Further research is required to determine the prevalence of hesitancy amongst vaccinating parents and identify critical points for intervention.